Pengembangan Konten Interaktif pada Course E-Learning Berbasis Moodle dengan Topik Presentasi Zen - Adlin Astridiani Juistha; Pujianto Yugopuspito (Syntax Idea)
This research aims to produce interactive media content for the e-learning course. This interactive media is included in the e-learning course and can be used by teachers at Pandu Pertiwi Foundation to guide them in making learning presentations based on Zen presentations. The research method used is Research and Development (R&D) with the ADDIE model. However, the model is modified with the stages carried out, namely analysis, design, development, and implementation. At the development stage, trials were carried out on material experts, learning design experts, and learning media experts, which were carried out in two cycles. At the implementation stage, user trials were carried out on three teachers who were representatives of the product to see its suitability for user needs. Based on expert and user trials, this H5P interactive content is feasible to use.